2020
DOI: 10.1101/2020.10.01.322974
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Perilipin2 down-regulation in β cells impairs insulin secretion under nutritional stress and damages mitochondria

Abstract: Perilipin 2 (PLIN2) is the lipid droplet (LD) protein in beta cells that increases under nutritional stress. Down-regulation of PLIN2 is often sufficient to reduce LD accumulation. To determine whether PLIN2 positively or negatively affects beta cell function under nutritional stress, PLIN2 was down-regulated in mouse beta cells, INS1 cells, and human islet cells. Beta cell specific deletion of PLIN2 in mice on a high fat diet reduced glucose-stimulated insulin secretion (GSIS) in vivo and in vitro. Down-regul… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
3
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
1
1

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 63 publications
0
3
1
Order By: Relevance
“…These results are not consistent with the current published work in rodents (24,37). However, they do partly agree with preprint findings in INS-1 cells (41). It is now unclear if this reflects species differences or the methodological approach.…”
Section: Limiting Ld Accumulation Induces Lipotoxic-like Er Stress and Dysfunctioncontrasting
confidence: 99%
See 1 more Smart Citation
“…These results are not consistent with the current published work in rodents (24,37). However, they do partly agree with preprint findings in INS-1 cells (41). It is now unclear if this reflects species differences or the methodological approach.…”
Section: Limiting Ld Accumulation Induces Lipotoxic-like Er Stress and Dysfunctioncontrasting
confidence: 99%
“…It is now unclear if this reflects species differences or the methodological approach. Although this recent work had only limited molecular detail in how compromising LD formation negatively impacted β cell function, their physiological results showed that mitochondrial health and activity was negatively impacted in both rodent β cells and human islets (41). Notably, our RNA data also suggests that the integrity of PLIN2KD mitochondria are compromised ( Supp Fig.…”
Section: Discussionmentioning
confidence: 99%
“…Lastly, we tested whether the morphology of two organelles (i.e., mitochondria and LDs) changes in human beta cells on C5533 in response to stimuli known to alter their morphology in a wide range of cells; FCCP is known to cause fragmentation of mitochondria, and nutritional load increases LDs ( 31 , 36 ). Both FCCP and high glucose + OA shortened the mitochondrial length and decreased the form factor in beta cells, providing evidence that both conditions fragment mitochondria in human beta cells in culture and support the utility of the protocol to obtain morphometric data ( Figures 5A–C , Supplementary Figures 3C–F ).…”
Section: Resultsmentioning
confidence: 99%
“…Briefly, images were converted to binary images of mitochondrial particles and automated morphometry of mitochondrial particles was performed to obtain mitochondrial length and form factor (perimeter 2 /(4π × area)) ( 29 , 30 ). The size and number of LDs were measured as published ( 31 ). The area of beta cells (INS + ) was also obtained by ImageJ/Fiji.…”
Section: Methodsmentioning
confidence: 99%